Exploring Active Learning Strategies in Science among Senior High School STEM Learners and Teachers - Ananias Jr Yunzal; Aubrey Ginelle Rallos; May Noren Nanud; Ma. Lina Ondoy; Jhun Matthew Ares; Marchee Picardal (Science Education International, 2024)
With the recent data revealing the performance status of Filipino learners in science aggravated by the negative effects of the pandemic, a concerted effort is directed toward exploring how learners learn science concepts in the current educational landscape to address issues of poor conceptual understanding and a learning gap. This qualitative study explored the perceptions of STEM learners on different ways of learning science concepts and how teachers developed the habits and attitudes of learning science among their students to develop conceptual understanding. Using a descriptive phenomenological approach, a semi-structured interview guide was conducted among 15 teachers with their corresponding students (n = 60) to explore their strategies and purposeful ways of learning and understanding concepts in science. Thematic analysis revealed five themes that describe STEM learners’ science learning process: extended reading, recalling, and rewriting; seeking help from MKO (more knowledgeable others); self-directed learning; acquisition from learning resources; and experiential learning. Both learners’ and teachers’ narratives emphasized the need for diverse approaches catering to the needs, interests, and contexts of every individual to promote the science of learning among students. While learners are struggling to concretize abstract concepts in science, their varied intentional science of learning enables them to navigate in the learning process.